Financial Risk Management Strategies in Startup Companies: Accounting Perspectives - Silaban, Barnabas Tridig; Setiana, Sinta; Tanujaya, Tyara Angel Clarissa (SEAN Institute, 2024)
Startup companies face significant financial risks due to the innovative nature of their business, high levels of uncertainty, and limited resources. This study aims to explore financial risk management strategies in startup companies from an accounting perspective using a mixed-methods approach. This method combines quantitative analysis of startup financial data with in-depth qualitative interviews with company founders, financial managers, and accountants. This research also involves support and data from various institutions such as the Financial Services Authority (OJK), the Indonesian Venture Capital Association (Amvesindo), and the Indonesian Startup Studio from the Ministry of Communication and Information Technology (Kominfo). The results of quantitative research show that the implementation of accrual-based financial reporting systems, risk-based budget utilization, and proactive cash flow management are the main practices in reducing financial risks. Meanwhile, qualitative findings reveal that understanding of financial risk is often limited, especially in early-stage startups. An effective risk mitigation strategy involves a combination of the use of digital accounting technology supported by institutions such as IDX Incubator, as well as strict management of debts and receivables with investor collaboration through platforms such as Amvesindo. This study concludes that the integration of modern accounting approaches with a deep understanding of startup risk dynamics can increase a company's resilience to financial challenges. The study recommends the development of a risk accounting-based training model with support from the Indonesian Institute of Public Accountants (IAPI) and University Research Institutes, as well as increased access to financial resources through the support of institutions such as BEKRAF and the Asian Development Bank (ADB). Further research is expected to explore the application of this strategy in a broader context and with a variety of industry sectors.